121k views
2 votes
Can any one help me?​

Can any one help me?​-example-1

2 Answers

4 votes

Answer:

64

Explanation:

2x-4y=3

x= (3 +4y)/2

substitute into the main equation

y= 0

x= 3/2

16^x /256^y

16^3/2 ÷ 256^0

√16^3 ÷1

= 64

User Kunal Kapadia
by
4.5k points
4 votes

Answer:

64

Explanation:

2x - 4y = 3

2x = 4y + 3

x = 2y + 1.5


(16^x)/(256^y) =


= (16^(2y + 1.5))/(256^y)


= (16^(2y + 1.5))/(16^(2y))


= 16^(2y + 1.5 - 2y)


= 16^(3)/(2)


= 4^3


= 64

User Higor Rossato
by
4.7k points